Self-monitoring of the resting heart rate using a fitness tracker smartwatch application leads to an early diagnosis of large vessel vasculitis. Issue 2 (28th February 2022) - Gkikopoulos, Nikitas; Wenger, Mathias; Distler, Oliver; Becker, Mike
Abstract : Giant cell arteritis can involve both cranial and extracranial arteries. Isolated extracranial large vessel vasculitis more often manifests with non-specific constitutional symptoms, causing a diagnostic delay. We report the case of a 57-year-old Caucasian female patient presenting with persistently elevated resting heart rate, as revealed by a smartwatch healthcare application, and non-specific constitutional symptoms. Imaging revealed inflammation of the aorta, bilateral subclavian and axillary arteries, compatible with large vessel vasculitis. Treatment with glucocorticoids and tocilizumab led to a significant improvement of her symptoms and decrease in inflammatory parameters. In sum, an unexplained elevated resting heart rate may lead to an earlier diagnosis and treatment of large vessel vasculitis, especially when other manifestations are non-specific. The use of healthcare smartwatch applications may prove useful in the future and lead to an earlier referral of patients to a physician.